2020
DOI: 10.1088/1367-2630/ab73cb
|View full text |Cite
|
Sign up to set email alerts
|

Cloud shape of a molecular Bose–Einstein condensate in a disordered trap: a case study of the dirty boson problem

Abstract: We investigate, both experimentally and theoretically, the static geometric properties of a harmonically trapped Bose-Einstein condensate of 6 Li 2 molecules in laser speckle potentials. Experimentally, we measure the in situ column density profiles and the corresponding transverse cloud widths over many laser speckle realizations. We compare the measured widths with a theory that is non-perturbative with respect to the disorder and includes quantum fluctuations. Importantly, for small disorder strengths we fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 82 publications
(121 reference statements)
2
15
0
Order By: Relevance
“…Recently, it has been demonstrated that the Huang-Meng theory can be verified quantitatively by using the homogeneous results within a local density approximation (LDA) [33]. Here we demonstrate that the above time-dependent results can also be extended to the case of inhomogeneous condensates in disordered traps, provided that the disorder correlation length is much smaller than the spatial extent of the atomic cloud.…”
Section: Condensates In Disordered Trapssupporting
confidence: 55%
See 3 more Smart Citations
“…Recently, it has been demonstrated that the Huang-Meng theory can be verified quantitatively by using the homogeneous results within a local density approximation (LDA) [33]. Here we demonstrate that the above time-dependent results can also be extended to the case of inhomogeneous condensates in disordered traps, provided that the disorder correlation length is much smaller than the spatial extent of the atomic cloud.…”
Section: Condensates In Disordered Trapssupporting
confidence: 55%
“…The consideration of scenarios when the disorder correlation function has a non-zero correlation length σ showed that both condensate and superfluid depletions decrease with increasing σ, in particular for the case of a Gaussian [21,[27][28][29], Lorentzian [30], or laser speckle disorder [31,32]. Quite recently, the predictions of the Huang-Meng theory were experimentally confirmed by analyzing the cloud shape of a molecular 6 Li BEC in a disordered trap [33]. Furthermore, building on an equilibrium inhomogeneous Bogoliubov theory [34], the results presented in [35] clarified the relation between the condensate depletion and condensate deformation in the presence of a weak, possibly random, external potential.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Finally, our approach can be adapted to investigate the transport properties of other kinds of two-particle systems subject to quenched randomness, like Cooper pairs in strongly disordered atomic gases [81] or superconductors [82][83][84]. Investigations of the steady-state and out-of-equilibrium properties of a Fermi gas undergoing the BCS-BEC crossover in the presence of a random potential [85] are already under way [86][87][88][89].…”
Section: Discussionmentioning
confidence: 99%